The effect of NiTi rotary systems activated with different kinematics on canal transportation and centring ability. A concise review (Mustansiria Dental Journal, 2022)
One of the most crucial steps in endodontic therapy is canal preparation. The root canal should have a flare shape from apex to coronal areas, with the apical foramen maintained in its original relationship to the surrounding tissues and root surface. Anatomical complexity causes most endodontic problems. Ledges, zips, perforations, and root canal transportation are more probable in curved canals because all preparation procedures and instruments deviate the prepared canal away from its initial axis. The type of kinematics employed, including continuous rotation, reciprocation movement, and adaptive movement, as well as root canal anatomy and instrument design features, all have been found as factors that may affect canal transportation. There are controversial results concerning the influence of kinematic on canal transportation. These results may be attributed to a lack of standardisation in file characteristics such as taper, size, and cross-section. Studies started using the same system under continuous rotation and reciprocation movement or adaptive motion to overcome these issues. This article reviews the effects of movement types on canal transportation and centring ability when all other variables are the same.